DOES SIZE MATTER? Technical Efficiency and Industry Size in Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
The debate over which size industry is best suited for Indonesia continues with proponents of both large and small sizes pointing out the benefits of each. However, little empirical analysis has been done regarding economic matters such as technical efficiency.